Formation of AGS in an Airlift Reactor with Divided Funnels Under Combined Selective Pressure - Awang, Nik Azimatolakma (International Journal of Integrated Engineering, 2019)
Understanding on the competence of aerobic granules sludge (AGS) system to recover the granulation process when instability occurs remained scarce since current research works on continuous variation in the organic loading rate (OLR) applied have been rarely reported. Thus, this study determines the dynamic granulation process and stability of AGS system by combining selective pressure generated by variation of OLR from 0.26 to 0.81 kg CODs m-3 d-1, use of an airlift reactor with divided funnel having a low height/diameter (H/D) ratio of 4.4 and low hydrodynamic shear force (superficial air velocity, SAV of 0.7 cm s-1).Â Matured AGS was attained after 67 days of the reactor setup with an optimal sludge volume index (SVI) of 33 ml g-1 and 15 min of settling time. The AGS system was generally stable between day 41 to 67 at average mixed liquor suspended solids (MLVSS) of 0.85 g L-1 and sludge retention time of 6 days. The next generation sequencing (NGS) analysis indicated that the shift in microbial community performing denitrification process from Rhodocyclaceae to Comamonadaceae class was accommodated with changes in aerobic granules size from 147 Âµm to over 336 Âµm.